Allicin Improves Intestinal Epithelial Barrier Function and Prevents LPS-Induced Barrier Damages of Intestinal Epithelial Cell Monolayers - Gao, Jingxia; Song, Guanzhong; Shen, Haibo; Wu, Yiming; Zhao, Chongqi; Zhang, Zhuo; Jiang, Qian; Li, Xilong; Ma, Xiaokang; Tan, Bie; Yin, Yulong (Frontiers in Immunology, 2022)
Gut barrier disruption is the initial pathogenesis of various diseases. We previously reported that dietary allicin improves tight junction proteins in the endoplasmic reticulum stressed jejunum. However, whether the allicin benefits the gut barrier within mycotoxin or endotoxin exposure is unknown. In the present study, IPEC-J2 cell monolayers within or without deoxynivalenol (DON) or lipopolysaccharide (LPS) challenges were employed to investigate the effects of allicin on intestinal barrier function and explore the potential mechanisms. Results clarified that allicin at 2 μg/mL increased the viability, whereas the allicin higher than 10 μg/mL lowered the viability of IPEC-J2 cells via inhibiting cell proliferation. Besides, allicin increased trans-epithelial electric resistance (TEER), decreased paracellular permeability, and enhanced ZO-1 integrity of the IPEC-J2 cell monolayers. Finally, allicin supplementation prevented the LPS-induced barrier damages via activating Nrf2/HO-1 pathway-dependent antioxidant system. In conclusion, the present study strongly confirmed allicin as an effective nutrient to improve intestinal barrier function and prevent bacterial endotoxin-induced barrier damages.